Efeitos da exposição crônica ao cloreto de mercúrio sobre a pressão arterial e a reatividade vascular de artérias mesentéricas de resistência de SHRs pré-hipertensos - Fardin, Paloma Batista Almeida (2019)
Mercury is a heavy metal associated with cardiovascular diseases. Studies reported increased vascular reactivity without changes in systolic blood pressure (SBP) after chronic mercury chloride (HgCl2) exposure in normotensive rats. However, we do not know whether individuals in the prehypertensive phase, such as young spontaneously hypertensive rats (SHRs), are susceptible to increased arterial blood pressure. We investigated whether chronic exposure to HgCl2 in young SHRs accelerates hypertension development by studying the vascular function of mesenteric resistance arteries (MRAs) and SBP in young SHRs during the prehypertensive phase. Four-week-old SHRs were divided into 2 groups: SHR control group and SHR HgCl2 group. The SHR control group received intramuscular injections of 0.9% NaCl for 30 days, while the SHR HgCl2 group received intramuscular injections of HgCl2 for the same period to achieve a final plasma concentration of approximately 29 nM, with an initial dose of 4.6 μg/kg and subsequent doses of 0.07 μg/kg/day. The animals were submitted to caudal plethysmography for indirect measurement of SBP on the first day of treatment and then weekly until the end of the 30-day treatment. At the end of treatment, the animals were anesthetized and euthanized, and the heart, mesenteric bed and blood were removed for analysis of cardiac hypertrophy, vascular reactivity and biochemical analyzes. The results showed that HgCl2 treatment accelerated the development of hypertension; reduced vascular reactivity to phenylephrine in MRAs; increased nitric oxide (NO) generation; promoted vascular dysfunction by increasing the production of reactive oxygen species (ROS), such as hydrogen peroxide (H2O2); increased Gp91Phox protein levels and in situ levels of superoxide anion (O2•-); and reduced vasoconstrictor prostanoids production compared to vehicle treatment. Although HgCl2 accelerated the development of hypertension, the mercury-exposed animals also exhibited a vasoprotective mechanism to counterbalance the rapid increase in SBP by decreasing vascular reactivity through H2O2 and NO overproduction. Our results suggest that HgCl2 exposure potentiated this vasoprotective mechanism, since, before that, it caused the early establishment of hypertension. Therefore, chronic exposure to HgCl2 in prehypertensive animals could enhance the risk for cardiovascular diseases, accelerating hypertension development.